2003
DOI: 10.1080/09658210244000522
|View full text |Cite
|
Sign up to set email alerts
|

"I couldn't have seen it coming": The impact of negative self-relevant outcomes on retrospections about foreseeability

Abstract: We examined a phenomenon related to hindsight bias, specifically, retrospective judgements about the foreseeability of an outcome. We predicted that negative, self-relevant outcomes would be judged as less foreseeable by the recipient of the outcome than by others, unlike either positive outcomes or outcomes that are not self-relevant. In the context of a "stock market decision-making game", the hypothetical stock selected by one of two players showed an extreme increase or decrease. As predicted, the player w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 49 publications
1
31
1
Order By: Relevance
“…The defensive processing approach argues that we can reduce our sense of culpability by denying the foreseeability of a negative event (Mark et al, 2003). Events that are not under one's control should not require defensive processing because they do not threaten the self.…”
Section: Outcome Controllabilitymentioning
confidence: 99%
“…The defensive processing approach argues that we can reduce our sense of culpability by denying the foreseeability of a negative event (Mark et al, 2003). Events that are not under one's control should not require defensive processing because they do not threaten the self.…”
Section: Outcome Controllabilitymentioning
confidence: 99%
“…Instead of believing in hindsight that they knew this all along, as a strictly cognitive view of hindsight bias would hold (unless the outcome is surprising-in which case, hindsight bias can be attenuated or even reversed; see Müller & Stahlberg, 2007, for an overview), quite a number of studies have shown that hindsight is reduced and often eliminated under such conditions (Louie, 1999(Louie, , 2005Louie, Curren, & Harich, 2000;Mark, Boburka, Eyssell, Cohen, & Mellor, 2003;Mark & Mellor, 1991;Pezzo & Beckstead, 2008). Importantly, this holds even if any possibly confounding influence of surprise is controlled for (Louie, 1999).…”
Section: Controllability and Hindsight Components: Understanding Oppomentioning
confidence: 98%
“…The key idea is that a negative event outcome reflects unfavorably on the self only if the person has some responsibility for it, which presupposes controllability. For instance, Mark et al (2003), comparing their own results with those of Tykocinski and colleagues, ar-making studies that showed a reduction or elimination of hindsight bias, the dependent measures are obvious measures of foreseeability and require no further comment (Louie, 1999;Mark et al, 2003;Mark & Mellor, 1991). In three others (Louie, 2005;Louie et al, 2000;Pezzo & Beckstead, 2008), the participants were asked (1) to make hindsight predictions of the outcome or (2) to recall predictions that they had actually made.…”
Section: Controllability and Hindsight Components: Understanding Oppomentioning
confidence: 99%
See 2 more Smart Citations